Retraction: Microelectrochemical cell arrays for whole-cell currents recording through ion channel proteins based on trans-electroporation approach. Issue 5 (31st January 2020) - Zheng, Tianyang; Baaken, Gerhard; Behrends, Jan C.; Rühe, Jürgen
Abstract : Retraction of 'Microelectrochemical cell arrays for whole-cell currents recording through ion channel proteins based on trans-electroporation approach' by Tianyang Zheng et al., Analyst, 2020, 145, 197–205.